Historic landscapes, diversified livelihoods in the southwestern Amazon: the case of Lake Rogaguado and Lake Ginebra (Bolivia) - Jaimes-Betancourt, Carla; Fernandez, Geraldine; Shock, Myrtle P.; Nina, Hortensia; Delgadillo, Henry; Prestes-Carneiro, Gabriela; Lima, Andrea; Nunes, Vinicius M.; Torrico, Renan (Frontiers in Environmental Archaeology, 2025)
This article presents the results of interdisciplinary and collaborative research conducted around Lakes Rogaguado and Ginebra, located in the north-central sector of the Llanos de Moxos, Bolivia—an area with limited archaeological exploration but prominent in ethnohistoric accounts related to the legendary “Gran Paititi.” Through systematic surveys, excavations, analyses of ceramics, zooarchaeological and paleoethnobotanical remains, and LiDAR mapping—carried out in dialogue with Cayubaba and Movima Indigenous communities—we identified monumental earthen architecture, raised agricultural fields, complex hydraulic systems, and a remarkable diversity in the use of local fauna and flora. The data reveal at least three main phases of pre-Hispanic occupation, each with distinct spatial and chronological patterns. At the Paquío site near Lake Rogaguado, two of these phases were documented: an early occupation around AD 600, possibly contemporaneous with the San Juan site, and a later, more intensive occupation between AD 1000 and 1200. This later phase is characterized by a higher density of ceramics, faunal and botanical remains, maize-based agriculture, and an elaborate hydraulic network associated with raised fields. In contrast, at the Jasschaja site, only the third phase of occupation was identified, dated to AD 1300–1400. Located near the El Cerro site on the eastern shore of Lake Ginebra, this phase shows broader landscape modifications, a greater diversity of plant use, and reduced faunal representation, suggesting an economy increasingly focused on the intensive management of cultivated and wild plant species. These differences reflect not only specific ecological adaptations but also broader transformations in social organization, settlement dynamics, and landscape management over time. By integrating archaeological, historical, and ethnographic evidence, this study repositions this region as a key node within the political, economic, and symbolic networks of the southwestern Amazon, shaped by continuous processes of mobility and landscape modification. This research underscores the importance of interdisciplinary, multiscalar, and community-engaged approaches for reconstructing socio-environmental dynamics of the Late Holocene in the Neotropics. It also offers new insights for the recognition of biocultural heritage and the pursuit of territorial justice in rapidly changing contexts.